2021
DOI: 10.1111/joa.13397
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional visualization of the bovine cardiac conduction system and surrounding structures compared to the arrangements in the human heart

Abstract: In the human heart, the atrioventricular node is located toward the apex of the triangle of Koch, which is also at the apex of the inferior pyramidal space. It is adjacent to the atrioventricular portion of the membranous septum, through which it penetrates to become the atrioventricular bundle. Subsequent to its penetration, the conduction axis is located on the crest of the ventricular septum, sandwiched between the muscular septum and ventricular component of the membranous septum, where it gives rise to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The atrioventricular node is located at the apex of the Koch triangle, whereas the bundle of His divides at the juncture of the fibrous and muscular boundaries of the IVS into the left and right bundle branches (LBB and RBB, respectively). The LBB subsequently divides into anterior and posterior fascicles, which course towards the anterior and posterior papillary muscles of the LV, whereas the RBB courses down the right side of IVS near the endocardium in its upper third, deeper in the muscular portion of the IVS in the middle third, and then again near the endocardium in its lower third [ 13 ].…”
Section: Ivs Structurementioning
confidence: 99%
“…The atrioventricular node is located at the apex of the Koch triangle, whereas the bundle of His divides at the juncture of the fibrous and muscular boundaries of the IVS into the left and right bundle branches (LBB and RBB, respectively). The LBB subsequently divides into anterior and posterior fascicles, which course towards the anterior and posterior papillary muscles of the LV, whereas the RBB courses down the right side of IVS near the endocardium in its upper third, deeper in the muscular portion of the IVS in the middle third, and then again near the endocardium in its lower third [ 13 ].…”
Section: Ivs Structurementioning
confidence: 99%
“…The study of the canine hearts was approved by the Institutional Animal Care and Use Committee of the Extremadura University, and conforms to the Guide for the Care and Use of Laboratory Animals. These datasets have already been analyzed to determine the overall arrangement of the atrioventricular conduction axis (De Almeida, Macías, et al 2021; De Almeida, Mori, et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Our own earlier studies, nonetheless, have suggested that sections revealing the arrangement of the cardiomyocytes in their long axis could provide direct evidence of interconnections between them, a point not previously stressed or investigated. The bovine non‐branching bundle, furthermore, is particularly suited to three dimensional assessment, since as already indicated, it can be injected with India Ink (De Almeida et al, 2015, 2017; De Almeida, Mori, et al, 2021; Lhamon, 1912). It can then be analyzed stereoscopically if rendered transparent (De Almeida et al, 2015, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Once it has received this information, to adapt its frequency to meet the needs of the body, it initiates the electrical impulse which evolves with a frequency adapted to the needs of the body [ 7 , 8 ]. To model the heart system three main nodes among the six heart nodes are considered, namely the sinus node (SA node), the atrioventricular node (AV node) and the Purkinje fibres (PF node) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%